ECOLOGICAL DA’WAH STRATEGIES IN PROMOTING ENVIRONMENTAL CONSERVATION IN AMBON CITY - Hakis, Hakis; Masri, Abdul Rasyid; Tike, Arifuddin; Said, Nurhidayat Muhammad; Muliyadi, Irvan; Bin Kamarzaman, Mohd Haidar (Al-Qalam, 2024)
The purpose of this research is to provide an alternative solution for ecological-based Da’wah in the efforts to protect the environmental destruction in the city of Ambon. Ambon is a region surrounded by hills that are prone to disasters such as landslides and floods. Ecological-based da’wah is considered an alternative solution to instill environmental values in the community for environmental conservation.This research is a qualitative descriptive type supported by quantitative data by using phenomenological approach. This research locates in the city of Ambon. Observation, interviews, questionnaires, documentation, and Delphi technique are used to collect the data related to the research questions. The data then are analyzed by using the following phases: data reduction, data presentation, interpretation, and drawing conclusions.The study identified at least five alternative solutions for ecological da’wah in environmental conservation efforts in Ambon, namely: implementation of "dakwah bil hal" (preaching by action), maximizing the use of media, changing preaching strategies, applying conservation concepts, and enforcing environmental laws. Among these solutions, it is found that the most effective alternative solution is the maximal use of media by publicizing the importance of preserving the environment. The implications of this research suggest that the government of Ambon, religious leaders, and environmental stakeholders should make efforts to use media to the fullest extent and educate the public about the environment through mass media or social media.Keywords: the city of Ambon, ecological based da’wah, environmental conservation.